Coronavirus Disease 2019 During Pregnancy: A Systematic Review of Reported Cases. Issue 12 (December 2020) - Gatta, Anna Nunzia Della; Rizzo, Roberta; Pilu, Gianluigi; Simonazzi, Giuliana
Abstract : (Abstracted from Am J Obstet Gynecol 2020;223:36–41) The presence of coronavirus disease 2019 (COVID-19) in pregnant patients raises concerns for adverse outcomes. The goal of this study was to collect information on mothers and neonates with COVID-19 and shed light on delivery timing and mode of delivery.